Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4062/biomolther.2019.065
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Mesenchymal Stem Cells towards Neuronal Lineage: Clinical Trials in Nervous System Disorders

Abstract: Mesenchymal stem cells (MSCs) have been proposed as an alternative therapy to be applied into several pathologies of the nervous system. These cells can be obtained from adipose tissue, umbilical cord blood and bone marrow, among other tissues, and have remarkable therapeutic properties. MSCs can be isolated with high yield, which adds to their ability to differentiate into non-mesodermal cell types including neuronal lineage both in vivo and in vitro. They are able to restore damaged neural tissue, thus being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 93 publications
0
70
0
Order By: Relevance
“…Moreover, many studies have found the expression of MAP2, but only after subsequent differentiation of derived NSC-like cells [56,72]. The discrepancies in the mentioned results might be a result of variable biological features of the cells according to their source, the donor, and the culture conditions [96,97]. However, a recent comparative analysis highlighted that the source of MSCs has a greater influence than the culture conditions applied for neural induction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have found the expression of MAP2, but only after subsequent differentiation of derived NSC-like cells [56,72]. The discrepancies in the mentioned results might be a result of variable biological features of the cells according to their source, the donor, and the culture conditions [96,97]. However, a recent comparative analysis highlighted that the source of MSCs has a greater influence than the culture conditions applied for neural induction.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the choice to focus our attention on mesenchymal stem cells application in neurodegenerative diseases, a whole picture of different stem cells characteristics, with advantages and drawbacks, is reported below. Stem cells can be categorized as embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), fetal stem cells (FSCs), perinatal stem cells (PSCs), and adult stem cells (ASCs) [126]. ESCs are pluripotent stem cells isolated from the inner cell mass of blastocysts before the stage of gastrulation [127,128].…”
Section: Mesenchymal Stem Cells Potential In Neuronal Differentiationmentioning
confidence: 99%
“…Various strategies have been developed over the years to transdifferentiate MSCs into neurons. Inducers used in these strategies are generally divided into four groups: small molecules, epigenetic modifications, psychotropic drugs and enriched media (medium coctails with chemical inducers) [12]. Alternatively, differentiation of neurons from MSCs was reported in different ways such as using co-culture conditions, exosomes and graphene substrates [13][14][15].…”
Section: Introductionmentioning
confidence: 99%